Step
*
1
1
of Lemma
eu-colinear-trivial
1. e : EuclideanPlane@i'
2. a : Point@i
3. b : Point@i
4. ¬(a = b ∈ Point)@i
5. Colinear(a;b;b)
⇐⇒ (¬(a = b ∈ Point)) ∧ (¬((¬(b = a ∈ Point)) ∧ (¬(b = b ∈ Point)) ∧ (¬b-a-b) ∧ (¬a-b-b) ∧ (¬a-b-b)))
⊢ Colinear(a;b;b)
BY
{ D 5
THEN D 6 }
1
.....antecedent..... 
1. e : EuclideanPlane@i'
2. a : Point@i
3. b : Point@i
4. ¬(a = b ∈ Point)@i
5. Colinear(a;b;b)
⇒ ((¬(a = b ∈ Point)) ∧ (¬((¬(b = a ∈ Point)) ∧ (¬(b = b ∈ Point)) ∧ (¬b-a-b) ∧ (¬a-b-b) ∧ (¬a-b-b))))
⊢ (¬(a = b ∈ Point)) ∧ (¬((¬(b = a ∈ Point)) ∧ (¬(b = b ∈ Point)) ∧ (¬b-a-b) ∧ (¬a-b-b) ∧ (¬a-b-b)))
2
1. e : EuclideanPlane@i'
2. a : Point@i
3. b : Point@i
4. ¬(a = b ∈ Point)@i
5. Colinear(a;b;b)
⇒ ((¬(a = b ∈ Point)) ∧ (¬((¬(b = a ∈ Point)) ∧ (¬(b = b ∈ Point)) ∧ (¬b-a-b) ∧ (¬a-b-b) ∧ (¬a-b-b))))
6. Colinear(a;b;b)
⊢ Colinear(a;b;b)
Latex:
Latex:
1.  e  :  EuclideanPlane@i'
2.  a  :  Point@i
3.  b  :  Point@i
4.  \mneg{}(a  =  b)@i
5.  Colinear(a;b;b)  \mLeftarrow{}{}\mRightarrow{}  (\mneg{}(a  =  b))  \mwedge{}  (\mneg{}((\mneg{}(b  =  a))  \mwedge{}  (\mneg{}(b  =  b))  \mwedge{}  (\mneg{}b-a-b)  \mwedge{}  (\mneg{}a-b-b)  \mwedge{}  (\mneg{}a-b-b)))
\mvdash{}  Colinear(a;b;b)
By
Latex:
D  5
THEN  D  6
Home
Index